THE VALUES OF ANCESTOR’S MESSAGES (PAPPASENG) IN BUGINESE TRADITION (CASE STUDY ON BONE REGENCY STUDENTS IN UIN ALAUDDIN MAKASSAR) - Abdul Rasak; Nasrum Nasrum; Helmy Syukur (UIN Alauddin Makassar, 2019)
This research discussed about values in Ancestor's Message (Pappaseng) of Buginese tradition (Study Case at Bone regency Students in English and Literature Department of UIN Alauddin Makassar). This research aimed to find out the kinds of Pappaséng and figure out the influences of Pappaseng in their life. The researchers applied qualitative method where the data analyzed through Sikki’s theory (1991) about the kind of Pappaseng and Debbarma’s theory (2014) about the kind of values. The researchers used interview sheet, recorder and note taking as the instruments of the research. The researchers found there are three kinds of Pappaseng owned by Bone regency students, such as: Pappaseng as advice, view of life and individual relationship tightening. The researchers also found Pappaseng has good influence to the students' life. The researchers concluded that Buginese Students still keep Pappaseng as their life guidance. Keywords: Pappaseng, Values, Ancestors, Message, Buginese TraditionABSTRAKPenelitian ini membahas tentang nilai-nilai dalam Pesan Leluhur (Pappaseng) tradisi Bugis (Studi Kasus pada mahasiswa Kabupaten Bone yang kuliah di jurusan Bahasa dan Sastra Inggris UIN Alauddin Makassar). Penelitian ini bertujuan untuk mengetahui jenis-jenis Pappaseng dan mengetahui pengaruh Pappaseng dalam kehidupan mereka. Peneliti menerapkan metode kualitatif di mana data dianalisis melalui teori Sikki (1991) tentang jenis Pappaseng dan teori Debbarma (2014) tentang jenis nilai. Peneliti menggunakan lembar wawancara, perekam dan pencatatan sebagai instrumen penelitian. Peneliti menemukan ada tiga jenis Pappaseng yang dimiliki oleh mahasiswa kabupaten Bone, seperti: Pappaseng sebagai saran, pandangan hidup dan perekat hubungan individu. Peneliti juga menemukan Pappaseng memiliki pengaruh yang baik terhadap kehidupan mahasiswa. Peneliti menyimpulkan bahwa mahasiswa Bugis masih mempertahankan Pappaseng sebagai pedoman hidup mereka.Kata kunci: Pappaseng, Nilai, Leluhur, Pesan, Tradisi Bugis